ON THE SELECTION OF SURGICAL TECHNIGUES IN THE TREATMENT OF PULMONARY – PLEURAL FORM OF ACUTE NECROTIZING PNEUMONIA IN CHILDREN - N. K. Barova; V. A. Tarakanov (Кубанский научный медицинский вестник)
Summary: suppurative lung and pleura are one of the urgent problems of pediatric surgery. Implementation in practice of VATS treatment proved an advantage of this method over traditional. However, issues of local influence on inflammatory processes in all these methods of surgical treatment to date remain unsolved.